The impact of NKG2A and NKG2D receptors and HLA-E and MICA ligands polymorphisms on post-transplant complications after paediatric allogeneic HSCT: a single-centre experience - Siemaszko, Jagoda; Ussowicz, Marek; Rybka, Blanka; Ryczan-Krawczyk, Renata; Kałwak, Krzysztof; Bogunia-Kubik, Katarzyna (Frontiers in Genetics, 2023)
Natural Killer cells are the first subpopulation of lymphocytes that reconstitute after allogeneic haematopoietic stem cell transplantation (HSCT). Their activity is regulated by various receptor-ligand interactions, including stimulation of the activating NKG2D receptor by the MICA molecule, and inhibitory NKG2A receptor interacting with the HLA-E. In this study the research effort focused on the effect of selected NKG2A and NKG2D receptors and their ligands (HLA-E and MICA molecules) polymorphisms that may affect the pathomechanisms of post-transplant complications after HSCT in children. One hundred donor-recipient pairs from a single paediatric transplantation centre were investigated. Altogether six single nucleotide substitutions (NKG2A rs7301582; NKG2D rs1049174, rs1154831; HLA-E rs1264457; MICA rs1051792, rs1063635) were genotyped, and the influence of polymorphisms was analysed on acute and chronic graft-versus-host disease (GvHD), cytomegalovirus (CMV) infection incidence, disease relapse and survival. The distribution of the evaluated polymorphisms did not differ between patients and their donors. The results showed a significant influence of HLA-E rs1264457 polymorphism in patients’ HLA-E*01:01 allele, which was associated with increased risk of CMV infection (p=0.050), especially in children positive for CMV IgG before transplantation (p=0.001). Furthermore, the effect of HLA-E*01:01 allele on CMV infections was more evident in children above the age of 7 years (p=0.031). Strong tendencies (0.05